An Overview of Refractory Gold Test Work and Research in Adelaide - Dunlop G; Fander H. W; Wong K; Malcolm J. McPhersqn; Neill B. K (The Australasian Institute of Mining and Metallurgy, 1991)
Commercial interest in refractory gold is increasing rapidly. This trend is supported by the work patterns of Amdel, where, apartfrom routine process- ing of free-milling and refractory ores, the majority of testing now includes biological and pressure oxidation studies to enhance gold recoveries. Central Mineralogical Services have examined, among other ores, an apparently unique type of refractory coating. A summary is given of experience at Optimet Laboratories, Pty., Limited. Research into nitric acid pre-oxidation, underway at the South Australian Institute of Technology since 1987, has shown significant improvements in gold recoveries, and in some cases, large reductions in reagent consump- tions. Three final-year student research projects were undertaken in 1990, jointly between the University of Adelaide and the S.A. Institute of Tech- nology. These projects involved biological pre-oxidation, pressure leaching, and Scanning Electron Microscope examination of refractory ores, and the resultant pre-oxidation and cyanidation products.